CHANGING BEHAVIOR OF SD/MI STUDENTS THROUGH CLEAN AND HEALTHY BEHAVIOR LIFESTYLE (PHBS) CAMPAIGN POST-DISASTER IN PIDIE JAYA DISTRICT - Wardiati Yusuf; Asnawi Abdullah; Agustina Agustina; Basri Aramico (Universitas Muhammadiyah Aceh, 2022)
Children are the most vulnerable group to experience various problems in the disaster area, especially health problems. Therefore, it is necessary to do health promotion for children to increase their awareness and knowledge regarding health issues. This activity aims to raise elementary school students about clean and healthy life behavior through oration, speech contest, distribution of health promotion media (comics), and the inauguration of clean and healthy life behavior agents of Pidie Jaya Regency. This activity involved 300 students from various elementary schools in Pidie Jaya Regency, 30 teachers, and 50 invited guests. In this activity, 930 health promotion media (comics) were successfully distributed to campaign participants and schools in Pidie Jaya Regency, and 8 clean and healthy life behavior agents of Pidie Jaya Regency were successfully chosen by embedding the pin. The government should follow up this activity by empowering the established agents so that they can become agents of change in the community.Keywords: Comic; Campaign, Health Promotion Media, clean and healthy life behavior, Students